DETERMINATION OF MOTIVATION, ENVIRONMENT, AND DISCIPLINE ON WORK EFFECTIVENESS THROUGH WORK SKILLS OF EMPLOYEES AT THE REGIONAL DISASTER MANAGEMENT AGENCY (BPBD) OF ANAMBAS ISLANDS REGENCY - Reinald Stevianes Lalenoh; Chablullah Wibisono; Mohd. Gita Indrawan (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of competency, job placement, and organizational support on employee performance at BPBD Anambas Regency with job satisfaction as an intervening variable. The research method uses a quantitative approach with saturated sampling technique involving 159 BPBD employees. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Square (PLS). The results show that competency has a significant positive effect on job satisfaction (0.738; p=0.000) and employee performance (0.180; p=0.044). Job placement has the strongest direct effect on employee performance (0.369; p=0.000) but does not significantly affect job satisfaction. Organizational support has a significant positive effect on job satisfaction (0.319; p=0.000) but not directly on employee performance. Job satisfaction is proven to have a significant positive effect on employee performance (0.348; p=0.001). Mediation analysis shows that job satisfaction mediates the relationship between competency (0.257; p=0.003) and organizational support (0.111; p=0.006) on employee performance, but not for job placement. The research model can explain 87.1% of the variation in employee performance. These findings provide theoretical and practical contributions to human resource management development in disaster management agencies.